CULTIVATION OF POTATO VARIETIES SUITABLE FOR THE SOIL AND CLIMATE CONDITIONS OF THE KHORAZM OASIS - Kalantarov Sanat Kadamboyevich (Web of Journals Publishing, 2023)
This article contains information about potato varieties grown in Khorezm region, care, fertilizing methods and irrigation periods.
Keywords: This article contains information about potato varieties grown in Khorezm region, care, fertilizing methods and irrigation periods.